FOUNDATIONS OF INDIAN AND MUSLIM EPISTEMOLOGY: A GENERAL OVERVIEW - Gul, Naseem (Universitas Islam Indonesia, 2021)
Epistemology is the most fundamental branch of philosophy. It discusses philosophically truth and falsehood, validity of knowledge, limits of knowledge and nature of knowledge, knower and known, etc. Defined narrowly, epistemology is the study of knowledge and justified belief. As the study of knowledge, epistemology is concerned with the following questions: What are the necessary and sufficient conditions of knowledge? What are its sources? What is its structure, and what are its limits? As the study of justified belief, epistemology aims to answer questions such as: How we are to understand the concept of justification? What makes justified beliefs justified? Is justification internal or external to one’s own mind? Understood more broadly, epistemology is about issues having to do with the creation and dissemination of knowledge in particular areas of inquiry. The subject matter of epistemology is the process, methods, objects, characteristics, conditions, validity, and fallacies of knowledge. It should be remembered here that epistemology uses the philosophical methods of induction and deduction, analysis and synthesis. The Greek word 'episteme' is the root of epistemology or study of knowledge. This philosophical term is commonly associated with the inquiry of truth and knowledge. The word may have few connotations. First, epistemology can be the quest for true and scientific knowledge as opposed to opinion or belief. Secondly, it may be seen as an organized body of thought about reality. In general it may be regarded that epistemology is the branch of philosophy that studies knowledge. It attempts to answer the basic question: What distinguishes true (adequate) knowledge from false (inadequate) knowledge? As a philosophical enquiry, together with logic, it sharpens our quest in all other philosophical domains like metaphysics, cosmology, ethics and philosophy of God. As Aristotle said,